PEMBANGUNAN, KETIMPANGAN SOSIAL, DAN KEBUTUHAN HUKUMNYA: MENUJU PENEGAKAN HUKUM YANG BERKEADILAN - Sholahudin (Al'Adalah, 2017)
The capitalistic model of development has given rise to a massive, paradoxical, socio-economic imbalance. One side can not be denied economic development has given rise to various faces of progress, contributing positively to its citizens in meeting the socio-economic needs of everyday life. With these advances, citizens can more easily access the various necessities of life. But all that is limited by a handful of people with money. Will, it turns out there are victims of development of victims (victims of development) are lying, which pushed the marginalized. Their existence is incorporated as 'community waste and waste development'. In the capitalistic society structures laden with socio-economic imbalances, laws increasingly oppress the alit or the marginal for the benefit and the interests of the capitalist elite. Law enforcement in capitalistic society is undeniably laden with injustice, just as the face of socio-economic injustice. Therefore, in addition to the demolition of socio-economic structures that are unequal, it is also necessary to develop a responsive and progressive legal system that is based on humanitarian values. The legal system is sensitive and quick to respond to the problems - social content of the community by putting forward the aspects of justice and legal benefits. The legalistic-positivistic approach of tariffs fails in justice and the usefulness of the law (substantive) for society. Law enforcement is necessary to generate sociological aspects of society, to be more just. If the law is released from its social context, then the law will be far from the sense of community justice.